A quality improvement project to reduce the intraoperative use of single‐dose fentanyl vials across multiple patients in a pediatric institution. Issue 1 (14th November 2015) - Buck, David; Subramanyam, Rajeev; Varughese, Anna
Summary: Objective: The use of a single‐dose vial across multiple patients presents a risk to sterility and is against CDC guidelines. We initiated a quality improvement (QI) project to reduce the intraoperative use of single‐dose vials of fentanyl across multiple patients at Cincinnati Children's Hospital Medical Center (CCHMC). Methods: The initial step of the improvement project was the development of a Key Driver Diagram. The diagram has the SMART aim of the project, key drivers inherent to the process we are trying to improve, and specific interventions targeting the key drivers. The number of patients each week receiving an IV dose of fentanyl, from a vial previously accessed for another patient was tracked in a high turnover operating room (OR). The improvement model used was based on the concept of building Plan–Do–Study–Act (PDSA) cycles. Tests of change included provider education, provision of an increased number of fentanyl vials, alternate wasting processes, and provision of single‐use fentanyl syringes by the pharmacy. Results: Prior to initiation of this project, it was common for a single fentanyl vial to be accessed for multiple patients. Our data showed an average percentage of failures of just over 50%. During the end of the project, after 7 months, the mean percentage failures had dropped to 5%. Preparation of 20 mcg single‐use fentanyl syringes by pharmacy, combined with education of providers on appropriate use, was successful in reducing failures to below our goal of 25%. Conclusions: Appropriately sized fentanyl syringes prepared by pharmacy, education on correct use of single‐dose vials, and reminders in the OR, reduced the percentage of patients receiving a dose of fentanyl from a vial previously accessed for another patient in a high‐volume otolaryngology room. Abstract :